The Impact Of Social Media Use On SME Progress - Nel Arianty; Julita Julita (AIBPM Publisher, 2019)
Nowadays, people are using social media as an information center than other media. One of the advantages of social media is having a lot of potential for the advancement of an effort. Social Media can be used to conduct communication in business, help the marketing of products and services, communicate with customers and suppliers, complement brands, reduce costs and for online sales. Social Media is a communication tool for SMEs to communicate, highlight and supervise information about consumers. The research aims to determine the influence of customer relationship management, market access, on the advancement of SMEs. The respondent of this research is the SME actors in the district of Percut Sei Tuan Deli Serdang Regency, North Sumatera which uses social media in conducting its business. The sample of this study was 65, using the probability sampling technique. Data analysis techniques use multiple regression analyses with the help of SPSS 20.00 as well as hypothesis tests through partial tests (test-t), simultaneous tests (F-test) and coefficient of determination test. The results showed that customer relationship management, market access, had a significant effect on SME progress. The implication of this research are that with social media applications, businesses get the opportunity to maintain good relations with customers, expanding market access for their business progress.